Legal Implementation of Article 21 of Law No. 5/1990 in Edelweiss Conservation at Mount Butak: Pelaksanaan Hukum Pasal 21 Undang-Undang Nomor 5 Tahun 1990 dalam Konservasi Edelweiss di Gunung Butak - Assidiqin, Muhammad Yusuf Fanany; Phahlevy, Rifqi Ridlo (Indonesian Journal of Law and Economics Review, 2025)
General Background: Environmental conservation is a crucial legal and ecological concern, especially regarding the protection of rare plants in conservation areas. Specific Background: Edelweiss (Anaphalis javanica) is one of Indonesia’s protected plants, yet violations continue to occur in the Mount Butak area. Knowledge Gap: Previous studies have not fully examined how Article 21 of Law No. 5 of 1990 is implemented in real practice and its enforcement challenges. Aims: This study aims to analyze the implementation of Article 21 in protecting Edelweiss within the Mount Butak conservation area. Results: The findings show that law enforcement remains weak due to limited public awareness and the absence of strict supervision from authorities.Novelty: The study integrates empirical and juridical perspectives to highlight the inconsistency between legal norms and field practices. Implications: Strengthening law enforcement and environmental education is recommended to enhance conservation effectiveness and ensure the sustainability of protected ecosystems. Highlights: Legal framework of environmental conservation in Indonesia Protection of Edelweiss under Article 21 of Law No. 5/1990 Weakness of law enforcement in conservation areas Keywords: Environmental Law, Conservation, Edelweiss, Article 21, Law Enforcement